Impact of strength exercises on the level of performance of male discus throwers of the F40 category - Jasem, Ayad R; Muhammed , Sadiq Y; Jameel, Abdulazeez N; Tuama, Hussain M (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
F40 category (short stature) athletes usually suffer from stability related problems. Due to these problems it is difficult for them to give their best performances, despite their regular strength training protocols. Hence, preparation and implementation of specific strength exercises might help them to perform better in discus throw. The present study aimed to find out the impact of specific strength exercises on the level of performance of male discus throwers of the F40 category. The atheltes from the Dhi Qar Committee constituted the population of the study. The sample was selected by purposive sampling method. A total of five participants were recruited of F40 category. In the present study, statistical significant results were obtained on comparison between pretest and posttest findings. The results of this study showed that the program of strength exercises applied significantly improved the level of performance of male discus throwers of the F40 category.